Knowledge and Attitude Regarding Sex Education among Adolescents of Kolhapur (Indian Journal of Public Health Research & Development, 2021)
Background: During adolescence knowledge regarding puberty, reproduction, pregnancy and sexual healthis very limited. The lack of knowledge and being sexually active during this phase increases the risk of orsexually transmitted diseases and unwanted pregnancies.Objectives: To assess the knowledge and attitude regarding sex education, to determine its association withdemographic variables and also to assess the correlation between the knowledge and attitude regarding sexeducation among the adolescents of Kolhapur.Methodology: A total of 109 adolescent students from two randomly selected junior college were enrolledfor this quantitative survey research. The students of any stream within the age group of 16-19 years andwilling to participate were involved. Questionnaire was used to collect data regarding demographic data,knowledge and attitude regarding sex education. Answers given by participants were evaluated and analysed.Descriptive analysis was done in MS Excel(2016). Chi square test was used to assess the associations in Rsoftware (version 3.6.1).Results: Twenty-eight percent participants had adequate knowledge. Most participants either given incorrectanswers (35%) or responded as they don’t know the answer (37%). Majority of participants held uncertainattitude (66%) Knowledge of the participants were significantly associated with education (P=4.11E-08),stream of education (P=1.54E-05) and their residential area (P=7.93E-06). Attitude was not significantlyassociated with any of the demographic variables (P
Keywords: Adolescent, Pregnancy, Sex education.